Activated T-cell subsets in benign lymphoid hyperplasias and B-cell non-Hodgkin's lymphomas. - Diaz, J. I. (1991)
Activated tumor-infiltrating T lymphocytes (TIL-T) were quantitated prospectively in excisional biopsy specimens of 49 B-cell non-Hodgkin's lymphomas (NHL) of various grades and compared with eight benign lymphoid hyperplasias (BLH) to identify any potential difference in host T-cell response. Immunotyping of tissue-cell suspensions was done by three-color flow cytometry, which was complemented by immunocytology by using cytocentrifuged preparations. Two activated T-cell subsets were studied: acutely activated TIL-T (CD3+ CD25+ HLADr-) and chronically activated TIL-T (CD3+ CD25- HLADr+). Results showed an association of the more aggressive intermediate/high-grade B-cell NHL with a higher percentage of late-phase activated TIL-T and a progressive increase with the grade of malignancy: 10.29%, 23.25%, 33.87%, and 47.78% (means) for BLH and for low-, intermediate- and high-grade B-cell NHL, respectively. Differences for this subset were significant (P less than 0.050) for the following comparisons: hyperplasia versus intermediate-grade NHL (P less than 0.0012), hyperplasia versus high-grade NHL (P less than 0.0002), and low versus high-grade NHL (P less than 0.0080). The percentage of acutely activated TIL-T cells did not show a statistically significant difference between the groups. The results suggest a host T-cell response to proliferating neoplastic cells in B-cell NHL. Paradoxically, the response does not appear to be protective for the host since the intensity is directly proportional to the grade of malignancy. However, the recognition of this response may have clinical applications since its amplification with biological response modifiers may result in effective adoptive immunotherapy of B-cell NHL. Further clarification of the specificity and biologic significance of host T-cell activation in B-cell NHL will require functional studies of isolated lymphocytic subpopulations from neoplastic tissue.